Gastrofashion from haute cuisine to haute couture fashion and food - Geczy, Adam; Karaminas, Vicki (London Bloomsburry Visual Arts, 2022)
For hundreds of years consumers and scholars alike have acknowledged that food is affected by the same rapid shifts in taste as clothing; just like fashion, food is consumed and sold as a fashionable commodity. Yet despite this, the reciprocal relationship between fashion and food has not been fully explored - until now. Gastrofashion from Haute Cuisine to Haute Couture examines the relationship between food and fashion in clothing, style, and dress in all its manifestations, from the restaurant to the catwalk, to cookbooks, diet fads, slow food, fast fashion, celebrity chefs, artists, and musical performers. It traces the relationship between food and fashion back to the Middle Ages, to the rise of social refinements in manners, speech, clothing, and taste, when behaviours and appearances reflected social status and propriety and where the social display of wealth and privilege were inseparable from food and clothing. Nowadays, designer eateries such as Pasticceria Prada and Armani Ristorante and the display of food on fashion catwalks are the precursors of the restaurants of pre-Revolutionary France and the spectacles of world fairs and exhibitions. This much-needed book offers a substantive and incisive discussion for all those interested in the complex interrelationship between food and fashion - scholars, students, and general readers alike
Includes bibliographical references (pages 223-234) and index.
Keywords: Fashion design; Clothing and dress